2008
DOI: 10.1007/s10029-008-0349-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term discomfort after plug and patch hernioplasty

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…These results have been reported in the literature [4] and are also included in the meta-analysis by Zhao et al [5]. We are pleased, therefore, that the study by Sanders et al has reshuZed the risk of chronic pain due to PerWx repair, thus, conWrming the results from our personal experience [6].…”
supporting
confidence: 82%
“…These results have been reported in the literature [4] and are also included in the meta-analysis by Zhao et al [5]. We are pleased, therefore, that the study by Sanders et al has reshuZed the risk of chronic pain due to PerWx repair, thus, conWrming the results from our personal experience [6].…”
supporting
confidence: 82%
“…Specifically, mesh fixation has been linked to postoperative pain in as many as 63% of hernia repair procedures, with pain that alters patients’ quality of life occurring in 4–12% of the cases 9, 11. Postoperative evaluation that compared mesh fixation with staples versus fibrin glue found that the prevalence of chronic pain was significantly higher in the stapled group (21%) than in the fibrin sealant group (4.7%) 16.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in hernia repair, mechanical fixation methods may be the source of neural irritation and persistent pain. 811 In tendon reconstruction, on the other hand, surgical repairs often fail as sutures pull out through the tendinous tissue with loading 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…However, a question of whether the changed techniques of hernia repair in recent years, mainly implanted mesh, have caused a rise in the incidence of chronic groin pain from 1 to 28.7% was raised [8]. Mesh implantation in the inguinal region can result in clinical problems such as foreign body sensation in the groin, discomfort and abdominal wall stiffness which may interfere with patient activities [9]. Mesh migration to the intestine, urinary bladder, femoral vein, preperitoneal space and the scrotum has been reported after all varieties of mesh repairs [10e13].…”
Section: Introduction Q4mentioning
confidence: 98%